Rnase Purification from Isolate Rns - Puranjan, Mishra; Singh, Lakhveer; Zularisam, A. W. (Penerbit UMP, 2014)
Bacteria are the most preferred sources of RNase due to their broad biochemical diversity. The present study involved oOptimization and partial purification of RNase from a bacterial isolate from soil sample. Out of 12 bacterial isolates one isolate (RNS 3) was selected based on relatively higher RNase activity in the culture broth. The various physico-chemical parameters wereare consecutively optimized for maximum enzyme production. The optimized parameters are at were temperature of 34°C, incubation period (20 h) and inoculum size (10% v/v). Among different carbon and nitrogen sources supplementation of glucose and peptone, respectively to the broth showed enhanced RNase production. An alkaline pH (8.5) was suitable for maximum enzyme production by the bacterial isolate RNS3.